The Scottish Parliament : a Scandinavian-style assembly? - Arter, David (Library of legislative studies., 2004)
This book is unique in analysing the new Scottish Parliament from a systematically comparative perspective. Its basic premise is that since devolution in 1999 Scotland can be considered a Scandinavian-style democracy.